Planetary health literacy: A conceptual model - Jochem, Carmen; von Sommoggy, Julia; Hornidge, Anna-Katharina; Schwienhorst-Stich, Eva-Maria; Apfelbacher, Christian (Frontiers in Public Health, 2023)
Education for planetary health could be one of the key levers of the much-needed civilizational turn toward a sustainable and healthy future. Education goes beyond information provision and passing on of knowledge and includes competencies to transfer knowledge from one decision situation to another. There are a range of different literacy concepts from various research perspectives that aim to improve such competencies. While many contain aspects highly relevant for planetary health, there is still no comprehensive and integrative planetary health approach. To fill this research gap, we present a conceptual model of planetary health literacy. By zooming into the model, further details on the necessary core competencies of accessing, understanding, appraising, and applying information in order to make judgements and take decisions regarding planetary health can be found. Zooming out of the model allows a holistic planetary health perspective and shows the potential and opportunities of planetary health literacy for the health of humans and ecosystems. Planetary health literacy encompasses both a life-course and a transgenerational approach, at the individual, societal, and global level. Future educational programs focusing on planetary health could integrate the conceptual model to increase planetary health literacy of individuals, including relevant health literacy agents, and of societies.